Factors Associated with the Completeness of Inpatient Medical Record Filling in Dr. R Sosodoro Djatikoesoemo, Bojonegoro, East Java - Tegar Wahyu Yudha Pratama; Didik Tamtomo; Endang Sutisna Sulaeman (Journal of Health Policy and Management, 2018)
Background: Medical records are central to all patient healthcare activities. Fundamentally, they form part of a doctor